A clinical psychologist’s perspective of mental disorders in patients of 70 years of age or more, who underwent digestive tract cancer surgeries - Zielińska, Dorota; Durlik, Marek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Behavioural and psychological disorders in surgical patients treated for malignant diseases are not always adequately appreciated and often neglected. However, they are very important in the therapeutic process because they may severely disturb physical and psychological rehabilitation, the patient’s effective struggle with malignancy, environmental relationships and quality of life. Professional preoperative psychological assessment is necessary to facilitate therapy for malignant diseases in those patients who are specifically exposed to a severely stressful situation. Aim : To investigate the incidence of depression, hallucinations and anxiety in patients undergoing surgery for malignancy of the digestive tract. The influence of those disorders on the period of hospitalisation, cooperation with medical staff and postoperative quality of life was analysed. Material and methods: A routine program of psychological and psychiatric care for patients with malignancy, who undergo extensive surgical procedures, was implemented in our department several years ago. The program allows for identification of patients with a high risk of psychiatric disorders to provide them with special psychological support. Sixty-nine patients with advanced malignancy were followed after the surgery between 2009 and 2010. All were examined by a professional psychologist. A QLQ C-30 (EORTC) questionnaire was used to assess the quality of life. Results: Psychotic disorders were present in 53.6% of examined patients. Depression was dominating (57%), followed by anxiety (28%) and hallucinations (15%). The mean hospital stay was different between those, respectively, with and without psychotic disorders (17 days vs. 15 days). Quality of life index for patients at risk was 3.8 vs. 5.1 for more psychologically stable patients. Conclusions : Approximately 50% of patients undergoing surgery for malignant diseases develop severe psychotic disorders in the postoperative period. Preoperative psychological assessment seems to be extremely useful in providing adequate postoperative psychological support for individual patients.